24=-3x-6y

Simple and best practice solution for 24=-3x-6y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 24=-3x-6y equation:


Simplifying
24 = -3x + -6y

Solving
24 = -3x + -6y

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
24 + 3x = -3x + 3x + -6y

Combine like terms: -3x + 3x = 0
24 + 3x = 0 + -6y
24 + 3x = -6y

Add '-24' to each side of the equation.
24 + -24 + 3x = -24 + -6y

Combine like terms: 24 + -24 = 0
0 + 3x = -24 + -6y
3x = -24 + -6y

Divide each side by '3'.
x = -8 + -2y

Simplifying
x = -8 + -2y

See similar equations:

| -2(1+6d)=expand | | 5x-6=8x | | v-1/2 | | 12(1+6d)=expand | | 8x+3=70 | | (x^2)=38 | | 5(n+2)-3=22 | | x^2+27x+28= | | 2/7x+1/2x=3/5x+1 | | 24x-8-13x+2=24x-6-13x+11 | | 1=4x-5x+8 | | -4x-9-x=-9 | | 7(y-4)-7= | | 6-5x=8x | | y/6+22=2y | | 4^3(8^1/3z^2) | | C=12m+(4m-10) | | -23+x=x+11 | | -7(3q-1)=expand | | 5x+76x=105 | | 2y+4+3y-5+y=29 | | 0.88*x=22 | | z^2+12=48 | | log(128)4=x | | (3x)^2/3=0 | | 18-x/3=16 | | (x^2)=80 | | (3x-2)^2/3=16 | | -(4/7)-(1/5) | | x+2/13=9/13 | | (x^2)=-45 | | 2w^3-32w^2+6w-16= |

Equations solver categories